(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Woman has been portrayed in myriad roles - as a motherand protector, woman as inspirer and cherisher, woman as the motivating primalforce-shakti protecting good and destroying evil, woman has been envisioned asa chaste, suffering wife, and also as charmer or lurer. These are some of thefacets familiar in literature. The image of woman in Indo-Anglian novel iscomplex and multifaceted. Generally, She is presented as the heroine of thenovel. Indo-Anglian fiction reflects how a girl is unwelcomed in the family andexplores the reasons behind the traditional view. The same exploration ispresented in the fiction of ‘BigThree’—Raja Rao, R.K. Narayan, Mulk Raj Anand, who turned their attention tothe realistic problems of the poor as well as the treatment of woman. Later on,the woman writers, like Kamala Markandaya, Anita Desai, Nayantara Sahgal,Shashi Deshpande, etc., explored the area of women’s cause and put forth theirwritings from the feministic point of view.